Exploring Patterns in Algebraic Thinking - Borralho, António (2012)
Nowadays algebraic thinking has become central to the mathematics curriculum. The development of algebraic thinking is seen as essential to the mastery of algebra. The transition between numbers and a higher level of abstraction is not trivial and in moving from arithmetic to algebra students experience genuine difficulties (Barbosa and Borralho, 2009 and Sinistsky, Ilany and Guberman, 2009). Teachers should diversify strategies, allowing their students to develop algebraic reasoning and symbol sense (Arcavi, 2006). Considering the classroom environment, the present study aims to understand the use of patterns in a context of research tasks as a way to improve the progress of algebraic thinking. We started out with two main research questions focused on: (1) algebraic reasoning and (2) mathematical communication.